Study of the Need for Public Facilities on Soekarno-Hatta Road, West Nias Regency - Arwadi Asmar Jaya Gulo; Abdiyanto; Ruri Prihatini Lubis (CV. Doki Course and Training, 2026)
This study aims to conduct a study related to the need for public facilities on Jalan Soekarno-Hatta, West Nias Regency, which is one of the main routes connecting tourist areas and economic centers in the area. This road has a strategic role in supporting community mobility and is the main access for tourists. However, based on public observations and perceptions, public facilities along the road are still inadequate, which has an impact on the comfort and safety of road users. This study uses survey and interview methods to explore public opinions regarding the condition of existing facilities, such as roads, sidewalks, street lighting, rest places, and other public facilities. The results of the study show that the community expects improvements in road quality, the addition of safe sidewalks, better street lighting, and other supporting facilities such as public toilets and rest areas, supporting technology. This increase in public facilities is not only expected by local residents, but also by tourists who cross the route. The study also highlights the importance of cooperation between local governments and the private sector to overcome budget constraints and create better facilities. It is hoped that the improvement of public facilities on Jalan Soekarno-Hatta will improve the quality of life of the community, support the local economy, and strengthen the tourist attraction of West Nias Regency.